The Intermediate accounting series : volume 2 - Robles, Nenita S.; Empleo, Patricia M. (Mandaluyong City, Philippines : Millenium Books, Inc., 2019)
The frameworks should be the bases for the presentation of the financial Statements that will will thoroughly discuss in a significantly simple manner considering the acquired competencies of the learners at that age.
CHAPTER 1. Inventories -- 2. Property, Plant and Equipment -- 3. Investment Property -- 4. Intangible Assets -- 5. Biological Assets -- 6. Non-Current Held for sale.
Includes bibliographical references.
Keywords: ACCOUNTING